Digital technologies for sensory and physical disabilities - Anagnostopoulou, Panagiota; Polyxeni, Ntaountaki; Stathopoulou, Agathi (Eximia, 2023)
This study examines the role of Information and Communication Technologies (ICTs) in the inclusion of students with sensory disabilities. Our main goal is to present the importance of ICTs and highlight their contribution to the smooth and equal inclusion of these children in the educational system and society. Thus, the research team of this paper presents specific examples of ICTs that aid children with visual and hearing impairments and physical disabilities. ICTs provide an attractive and supportive environment for the students with special needs as well as equal opportunities regarding their inclusion. Since we live in the world of information and the digital revolution, we have to adapt to modern reality and prioritize the use of ICTs in education.